Atlantic mackerel population structure does not support genetically distinct spawning components [version 2; peer review: 1 approved, 2 approved with reservations] - Imanol Aguirre-Sarabia; Alice Manuzzi; Dorte Bekkevold; Natalia Díaz-Arce; Jessica Gomez-Garrido; Teunis Jansen; Marta Gut; Tyler S. Alioto; Sonia Sanchez-Maroño; Martin Castonguay; Naiara Rodriguez-Ezpeleta; Paula Álvarez (Open Research Europe)
Background The Atlantic mackerel, Scomber scombrus (Linnaeus, 1758) is a commercially valuable migratory pelagic fish inhabiting the northern Atlantic Ocean and the Mediterranean Sea. Given its highly migratory behaviour for feeding and spawning, several studies have been conducted to assess differentiation among spawning components to better define management units, as well as to investigate possible adaptations to comprehend and predict recent range expansion northwards. Methods Here, the genome of S. scombrus was sequenced and annotated, as an increasing number of population genetic studies have proven the relevance of reference genomes to investigate genomic markers/regions potentially linked to differences at finer scale. Such reference genome was used to map Restriction-site-associated sequencing (RAD-seq) reads for SNP discovery and genotyping in more than 500 samples distributed along the species range. The resulting genotyping tables have been used to perform connectivity and adaptation analyses. Results The assembly of the reference genome for S. scombrus resulted in a genome of 741 Mb. Our population genetic results show that the Atlantic mackerel consist of three previously known genetically isolated units (Northwest Atlantic, Northeast Atlantic, Mediterranean), and provide no evidence for genetically distinct spawning components within the Northwest or Northeast Atlantic. Conclusions Therefore, our findings resolved previous uncertainties by confirming the absence of genetically isolated spawning components in each side of the northern Atlantic, thus rejecting homing behaviour and the need to redefine management boundaries in this species. In addition, no further genetic signs of ongoing adaptation were detected in this species.